Agreement between physicians’ and nurses’ clinical decisions for the management of the fracture liaison service (4iFLS): the Lucky Bone™ program - Senay, A. (Osteoporos Int, 2015)
SUMMARY: We determined if nurses can manage osteoporotic fractures in a fracture liaison service by asking a rheumatologist and an internist to assess their clinical decisions. Experts agreed on more than 94 % of all nurses’ actions for 525 fragility fracture patients, showing that their management is efficient and safe. INTRODUCTION: A major care gap exists in the investigation of bone fragility and initiation of treatment for individuals who have sustained a fragility fracture. The implementation of a fracture liaison service (FLS) managed by nurses could be the key in resolving this problem. The aim of this project was to obtain agreement between physicians’ and nurses’ clinical decisions and evaluate if the algorithm of care is efficient and reliable for the management of a FLS. METHODS: Clinical decisions of nurses for 525 subjects in a fracture liaison service between 2010 and 2013 were assessed by two independent physicians with expertise in osteoporosis treatment. RESULTS: Nurses succeeded in identifying all patients at risk and needed to refer 27 % of patients to an MD. Thereby, they managed autonomously 73 % of fragility fracture patients. No needless referrals were made according to assessing physicians. Agreement between each evaluator and nurses was of >97 %. Physicians’ decisions were the same in >96 %, and Gwet AC1(1) coefficient was of >0.960 (almost perfect level of agreement). All major comorbidities were adequately managed. CONCLUSIONS: High agreement between nurses’ and physicians’ clinical decisions indicate that the independent management by nurses of a fracture liaison service is safe and should strongly be recommended in the care of patients with a fragility fracture. This kind of intervention could help resolve the existing care gap in bone fragility care as well as the societal economic burden associated with prevention and treatment of fragility fractures.